RNA-Sequencing of Heterorhabditis nematodes to identify factors involved in symbiosis with Photorhabdus bacteria - Bhat, Chaitra G.; Budhwar, Roli; Godwin, Jeffrey; Dillman, Adler R.; Rao, Uma; Somvanshi, Vishal S. (BMC genomics, 2022)
Nematodes are a major group of soil inhabiting organisms. Heterorhabditis nematodes are insect-pathogenic nematodes and live in a close symbiotic association with Photorhabdus bacteria. Heterorhabditis-Photorhabdus pair offers a powerful and genetically tractable model to study animal-microbe symbiosis. It is possible to generate symbiont bacteria free (axenic) stages in Heterorhabditis. Here, we compared the transcriptome of symbiotic early-adult stage Heterorhabditis nematodes with axenic early-adult nematodes to determine the nematode genes and pathways involved in symbiosis with Photorhabdus bacteria. A de-novo reference transcriptome assembly of 95.7 Mb was created for H. bacteriophora by using all the reads. The assembly contained 46,599 transcripts with N50 value of 2,681 bp and the average transcript length was 2,054 bp. The differentially expressed transcripts were identified by mapping reads from symbiotic and axenic nematodes to the reference assembly. A total of 754 differentially expressed transcripts were identified in symbiotic nematodes as compared to the axenic nematodes. The ribosomal pathway was identified as the most affected among the differentially expressed transcripts. Additionally, 12,151 transcripts were unique to symbiotic nematodes. Endocytosis, cAMP signalling and focal adhesion were the top three enriched pathways in symbiotic nematodes, while a large number of transcripts coding for various responses against bacteria, such as bacterial recognition, canonical immune signalling pathways, and antimicrobial effectors could also be identified. The symbiotic Heterorhabditis nematodes respond to the presence of symbiotic bacteria by expressing various transcripts involved in a multi-layered immune response which might represent non-systemic and evolved localized responses to maintain mutualistic bacteria at non-threatening levels. Subject to further functional validation of the identified transcripts, our findings suggest that Heterorhabditis nematode immune system plays a critical role in maintenance of symbiosis with Photorhabdus bacteria.